2023
DOI: 10.1097/hcr.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety, Depression, and Distress in SCAD and Non-SCAD AMI Patients

Abstract: I ncreasing research attention is being paid to the psychosocial consequences of spontaneous coronary artery dissection (SCAD), a cause of acute myocardial infarction (AMI) that is particularly common in young women with few classic cardiac risk factors. [1][2][3][4] Spontaneous coronary artery dissection accounts for up to 35% of AMIs in women aged < 50 yr, 3,4 and is the most common cause of pregnancy-related AMI. 5,6 Unlike typical AMI, which is generally due to atherosclerosis, SCAD-AMI is nonatherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
(236 reference statements)
0
6
0
Order By: Relevance
“…Several studies undertaken in the US, Canada, Australia, and Europe have documented relatively high rates of anxiety and depression in the aftermath of SCAD [11][12][13][14][15][16][17]. Emerging evidence suggests that SCAD-AMI may be more stressful than typical atherosclerotic AMI, with higher rates of post-event anxiety and depression [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies undertaken in the US, Canada, Australia, and Europe have documented relatively high rates of anxiety and depression in the aftermath of SCAD [11][12][13][14][15][16][17]. Emerging evidence suggests that SCAD-AMI may be more stressful than typical atherosclerotic AMI, with higher rates of post-event anxiety and depression [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies mark emotional stress as a trigger for SCAD because it correlates with catecholamines ( 7 , 16 , 33 37 ). It is believed that catecholamines may cause structural changes in the arterial wall leading to intimal rupture or disruption of the vasa vasorum, possibly through increased myocardial contractility or vasospasm ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a large US national database, including more than 66,000 patients with SCAD, showed that anxiety and depression were less frequent in SCAD patients compared with patients with atherosclerotic MI ( 30 ). Recently, Muphy et al ( 53 ) found that among SCAD patients, there was a higher prevalence of anxiety, depression, and other psychological disturbances compared with atherosclerotic MI. There is a need for further research in this area, utilizing standardized questionnaires completed early after hospital admission and incorporating subsequent psychiatric evaluations.…”
Section: Discussion: Clustering Of Scad Risk Factorsmentioning
confidence: 99%